Design of HPLC methods of fexofenadine quantitative analysis in blood plasma - E. N. Yakusheva; I. V. Chernykh; A. V. Shulkin; M. V. Gatsanoga (LLC "Publisher OKI", 2017)
The article describes a method of quantitative analysis of III generation gistamine antagonist - fexofenadine in human bLood plasma by HPLC with UV detection at 220 nm. The analysis was performed in isocratic mode using Stayer chromatography system and a reversed-phase column Phenomenex Synergi 4u PoLar-RP 80A (250 х 4,6, 4 |±m) and a mobile phase (acetonitriLe-water-gLaciaL acetic acid-triethyLamine in the ratio 267-128-4,7-7) at pH 6,1. The retention time of fexofenadine was 14,70±0,04 min. Fexofenadine extraction from pLasma carried using acetonitriLe (2 mL pLasma and 4 mL acetonitriLe) by shaking on Shaker apparatus at 400 voL/min for 15 minutes, centrifuging at 3 500 rpm. for 15 minutes and evaporation of the supernatant on a vacuum rotary evaporator at 50 °C. The recovery was 84,14%. The deveLoped method is characterized by sensitivity, specificity, ease of impLementation, reproducibiLity and Linearity in the range of pLasma concentrations during oraL administration of 180 mg of fexofenadine (ALLegra coated tabLets, 180 mg, Sanofi-Aventis, USA) heaLthy voLunteers.